Public Debt Vulnerabilities in Low-Income Countries : The Evolving Landscape. (Policy Papers; Policy Paper, 2015)
This is the first joint IMF/World Bank report on public debt vulnerabilities in low income countries (LICs). It examines debt-related developments and their underlying causes since the onset of the global financial crisis. The findings will inform the upcoming review of the IMF/WB debt sustainability framework for LICs. Over this period, improved macroeconomic performance in LICs, combined with HIPC/MDRI debt relief and high demand for commodities, contributed to improved LIC creditworthiness. At the same time, new borrowing opportunities emerged as a result of the accommodative liquidity conditions in international capital markets, the deepening of domestic financial markets for some LICs, and the growing lending activities of non-Paris Club countries. These new financing possibilities helped mitigate the decline in Paris Club lending to LICs and have been associated with a shift toward greater reliance on non-concessional credit. The changing financing landscape has been most significant for frontier LICs.